ON THE CONCEPT OF THE DEVELOPMENT OF NEW FEDERAL STATE HIGHER EDUCATION STANDARDS - Elena K. Gitman; Mikhail B. Gitman; Yaleriy Yu. Stolbov; Irina D. Stolbova (Высшее образование в России)
The article offers a concept of the development of new federal state standards for higher education. The distinctive feature of the proposed standards is to establish relations between the education objectives and disciplinary field of an education program. This allows to link more closely the developed standards to the international system of personnel training and contributes to the creation of a common education space both within the country and international cooperation. This can be ensured by making up catalogues with lists of disciplines and annotations of education programs. Applying to Russian conditions such catalogues canbe elaborated for aggregate groups of disciplines. An integrated quality assessment of learning outcomes includes a case study collection for evaluation of professional goals achievement. The ability to solve case study tasks can be considered as a main criterion of a graduate’s training quality.